Association analyses between urinary concentrations of multiple trace elements and gastric precancerous lesions and gastric cancer in Anhui province, eastern China - Qian, Shiqing; Xu, Fang; Wang, Min; Zhang, Meng; Ding, Shaopeng; Jin, Guoqing; Zhang, Xiaohui; Cheng, Wenli; Wang, Li; Zhu, Yuting; Wang, Wuqi; Ofosuhemaa, Princess; et al. (Frontiers in Public Health, 2024)
Limited epidemiological evidence suggests that the exposure to trace elements adversely impacts the development of gastric precancerous lesions (GPL) and gastric cancer (GC). The study aimed to estimate the association of individual urinary exposure to multiple elements with GPL and GC. A case-control investigation was conducted in Anhui Province from March 2021 to December 2022. A total of 528 subjects (randomly sampled from 1020 patients with GPL, 200 patients with GC, and 762 normal controls) were included in our study. Urinary levels of iron (Fe), copper (Cu), zinc (Zn), nickel (Ni), strontium (Sr) and cesium (Cs) were measured using inductively coupled plasma mass spectrometry (ICP-MS). Four different statistical approaches were employed to explore the risk of GPL and GC with mixed exposure, including multivariate logistic regression, weighted quantile regression (WQS), quantile g-computation (Qgcomp) and the Bayesian kernel machine regression (BKMR) model. The WQS model indicated that urinary exposure to a mixture of elements is positively correlated with both GPL and GC, with ORs for the mixture exposure of 1.34([95% CI]: [1.34-1.61]) for GPL and 1.38([95% CI]: [1.27-1.50]) for GC. The Qgcomp and BKMR Models also demonstrated a statistically significant positive correlation between the mixture and both GPL and GC. Considering the limitations of case-control studies, future prospective studies are warranted to elucidate the combined effects and mechanisms of trace elements exposure on human health. Keywords： Trace elements; Gastric precancerous lesions; Gastric cancer; Weighted quantile regression model (WQS); BKMR